User Experience Testing on the UII Informatics Department Website using the User Experience Questionnaire - Aulia Safira Ahda; Chanifah Indah Ratnasari (Sistemasi: Jurnal Sistem Informasi, 2023)
The website is one of the media used by some educational institutions to convey information. One of them is the Department of Informatics at the Universitas Islam Indonesia (UII). One of the basic things that need to be considered when developing a academic website is the user experience (UX) a user has when engaging with a website. User experience measures the comfort level of a user when interacting with a product. User experience needs to be evaluated regularly so that the website can continue to meet the expectations of its users. However, there has been no research related to evaluating or testing user experience on the UII Informatics Department website. This study aims to assess the level of experience of UII Informatics Department website visitors. This study employed quantitative research methods, specifically the User Experience Questionnaire (UEQ) method. Using the mean calculation, the UII Informatics Department website received positive assessments on the dimensions of perspicuity, efficiency, attractiveness, dependability, and stimulation, but received negative evaluations on the novelty dimension. According to the benchmark analysis, the aspects of perspicuity and efficiency are above-average. While the dimensions of novelty, stimulation, dependability, and attractiveness are below-average. The results of this study can be used as a reference for developing a website for the Department of Informatics with a version that is more in line with user needs.